Antibioprophylaxy by the Surgery Staff in the Teaching Hospital Gabriel Touré in Mali - Dembélé, Bakary Tientigui; Traoré, Alhassane; Togo, Adégné; Kanté, Lassana; Diakité, Ibrahim; Traoré, Amadou; Cissoko, Bourama Emmanuel; Konaté, Madiassa; Karembé, Boubacar; Coulibaly, Yacaria; Keita, Soumeila; Keita, Mamby; et al. (Scientific Research, 2015)
This prospective survey was conducted from February to December 2014 about the use ceftriaxone (ceftriaz) for antibioprophylaxy concerning 300 patients by the surgery staff in the Gabriel Touré Teaching Hospital in Mali. The quantity of drug used was based on the weight of the patient. One dose was administrated in intravenous at the anesthesiology induction time. For more than 2 hours of intervention time, 4 (1.3%) patients received a second dose. The majority of cases (189, 63%) were out of emergency (emergency cases—111, 37%). The mean age was 41.6 years (range: 3 - 95 years). The patients were classed Altmeir II 203 (67.7%) and Altmeir I 97 (32.3%). The NNISS score 0 concerned 101 (33.6%) and NNISS 1 in 180 (60%) patients. The factors of risky were anemia (38; 12.7%), diabetes (6; 2%), and HIV (3; 1%). The mean of intervention duration was 56.8 ± 27.5 minutes. Four cases of intervention site infection were encountered caused by Pseudomonas aeruginosa in 2 patients; Escherichia coli (1 case), and Staphylococcus aureus (1 case). Conclusion: Antibioprohylaxy is not the only way to prevent infections but it stays necessary. The respect of hygien and aseptic measures should be used to reduce the rate of intervention site infection.
Keywords: Antibioprophylaxy; Infection Risky Factors; Surgery